Exploring the Dark Figure of Hate: Experiences with Police Bias and the Under-reporting of Hate Crime - Erentzen, Caroline (Canadian journal of criminology and criminal justice, 2020)
Hate crimes are notoriously under-reported, and the present research explores possible etiological factors for this phenomenon in a national Canadian sample. Controlling for demographic and off ence characteristics, the research shows that victims who had prior experiences with police discrimination were significantly less likely to report hate crimes to police compared to victims of non-hate-based crimes. Additionally, victims experienced hate crimes in a more intersectional way than is typically reflected in police reports, as victims tended to interpret the offence as targeting multiple overlapping identities rather than a solitary hate motivation. Th ese fi ndings reflect the unique nature of hate-motivated off ences, whose victims may find it futile to report bias-motivated offences to a police force whom they believe is itself biased. These results suggest possible opportunities to improve reporting of offences and relations between police and marginalized communities.